Assessing the Effectiveness of Fire Safety Management from the FSM Stakeholders' Perspective: A Pilot Study - Ebenehi, Ibrahim Yakubu; Mohamed, Sulzakimin; Sarpin, Norliana; Adaji, Adejoh Ahmodu; Omar, Roshartini; Wee, Seow Ta (Journal of Technology Management and Business, 2019)
Malaysian education sector of the economy, particularly the higher education, had been making huge investments towards fulfilling a target of producing an attractive environment, conducive to learning and academic excellence. Building facilities account for a significant portion of investments in the sector. It has become imperative to research ways of ensuring the safety of built facilities and users from fire disaster since no building has immunity against fire. This research aims to develop a framework for effective fire safety management (FSM) for buildings in Malaysian Higher Education Institutions. This report displays the results of the pilot study conducted among staff from the facilities management, occupational safety health and environment (OSHE) and security departments from selected universities in Johor Malaysia prior to carrying out the core survey to collect information from target respondents. The pilot study shall help to minimise errors in the questionnaire, ensures the smooth running of the survey, facilitate the response rate, and provide a useful and valuable inquiry. The results include the descriptive statistics, reliability test, content and construct validity, the normality test, and factorability. The summary of the reliability test for each construct of the FSM Stakeholders' questionnaire, are Management and maintenance, 0.962; fire safety equipment/system, 0.921; building components safety design, 0.965, and the effectiveness of fire safety management have a value 0.916 for Cronbach alpha coefficient. The aggregate Descriptive Statistics results for the stakeholders' questionnaire show mean values between the ranges of 3.08 to 4.07. The questionnaire had low dispersion and standard deviation values of less than 1. The values of skewness and kurtosis were all within the recommended limit of -/+2, which indicates the normal distribution of all the constructs of the study. The results are a positive indicator to use the instrument for the primary survey.